Six-row winter barley Lancelot - Pavel MAŘÍK; Jana CHRPOVÁ; Ilja Tom PRÁŠIL; Tibor SEDLÁČEK (Czech Journal of Genetics and Plant Breeding, 2015)
The Lancelot variety is a late to semi-late six-row feeding winter barley. It was developed at the Breeding Station, Lužany, SELGEN a.s. and registered in the Czech Republic in 2013. Lancelot has very good resistance to winter stresses in combination with resistance to BaMMV/BaYMV (Barley mild mosaic virus/Barley yellow mosaic virus) based on the gene rym4.